Partial Seizures, Etiologies and Associated Comorbidity Factors - M Kadhim, Mezher; I Kadhim, Jalil; H Basee, Haitham; A Mohammed, Ammar; A Obaid, Kareem (Diyala Journal of Medicine, 2020)
Background: Partial seizure is well-defined as sudden extreme, profligate, and limited electrical discharges by gray matter from some portions of the brain due to certain structural & metabolic abnormalities. Objective: To distinguish the etiologies of partial seizures and to clarify its association with the age of affected patients. Patients and Methods: A prospective study, done on all patients with neurological consultation in Al- Batool Teaching Hospital, Baqubah Teaching Hospital and Al Yarmouk teaching Hospital from Nov, 2016 to Dec, 2018. Patients with partial seizures and/with secondary generalization were merged. This was fortified through a full history, physical checkup, EEG, and MRI of the brain. The study’s sample comprising 106 patients with partial seizures, the age ranged from 6-75 years, with 52 males and 54 females. Results: Atypical neuroimaging was found in (61%) of patients. Tumors occurred in (19.7%) of patients, the highest of them below 40 years of age while infarctions comprised 25.5% of patients outside this age. Complex partial seizures(CPS) patients with temporal lobe foci comprised 83.7 % and (16.2%) had frontal lobe problems, while (49%) of Simple partial seizures (SPS) patients had frontal lobe foci, 22% frontoparietal and 13% had parietal lobe foci and had brain lesions were spotted in 75.4% of patients with SPS and (35.1%) with complex partial seizures. Conclusion: Infarction is a common reason for partial seizures in patients above 40 years while below this age the tumor is common etiology. A partial seizure is connected mostly with brain lesions.